Heteroglycoclusters through Unprecedented Orthogonal Chemistry Based on N‐Alkylation of N‐Acylhydrazone. Issue 33 (1st April 2022) - Fray, Marwa; Mathiron, David; Pilard, Serge; Lesur, David; Abidi, Rym; Barhoumi‐Slimi, Thouraya; Cragg, Peter J.; Benazza, Mohammed
Abstract: Orthogonal chemistry is a valuable tool in the preparation of complex molecules as heteroglycoclusters. Unfortunately, selective heteroconjugation of multifunctional starting materials remains a usually challenging problem to overcome. Herein, we report the first report on harnessing N ‐alkylation of N ‐acylhydrazone as a key step in the orthogonal synthesis. Sequentially associated with the azido‐alkyne click chemistry, it stands out as a new and straightforward synthetic method of glycoconjugate small molecules, heterodisaccharides, and heteroglycoclusters based on cone p ‐ t Bu‐calix[4]arene and 1, 3‐ alt p ‐ t Bu‐thiacalix[4]arene with potential drug‐like properties. Abstract : We report a new orthogonal strategy involving the N ‐alkylation of N ‐acylhydrazone as a key step. When followed by azido‐alkyne click chemistry, it represents a new and straightforward synthetic method to prepare N ‐alkyl‐NAH glycoconjugates of small molecules, heterodisaccharides, and heteroglycoclusters‐based on cone p ‐ t Bu‐calix[4]arene and 1, 3‐ alt p ‐ t Bu‐thiacalix[4]arene with potential drug‐like properties.